2019
DOI: 10.2134/agronj2018.03.0214
|View full text |Cite
|
Sign up to set email alerts
|

Winter Cereal Cover Crops for Spring Forage in Temperate Climates

Abstract: In this study four winter cereals commonly used as cover crops were evaluated for forage yield potential and nutritional quality when harvested in early spring. Wheat (Triticum aestivum L.), triticale (X Triticosecale Wittm.), cereal rye (Secale cereale L.), and barley (Hordeum vulgare L.) were evaluated via experimental plots and on-farm trials in southern Ontario, Canada, between 2013 and 2015. Barley was the only species that failed to overwinter. The average forage yield of all other winter cereal species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
5
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 29 publications
6
28
5
2
Order By: Relevance
“…Winter cover crops can provide additional economic value and incentive for producers to adopt this practice. Winter cereal cover crops can be successfully utilized as a spring forage source [60][61][62]. The impacts on the subsequent cash crop can be variable, however.…”
Section: Winter Cover Crops For Spring Foragementioning
confidence: 99%
“…Winter cover crops can provide additional economic value and incentive for producers to adopt this practice. Winter cereal cover crops can be successfully utilized as a spring forage source [60][61][62]. The impacts on the subsequent cash crop can be variable, however.…”
Section: Winter Cover Crops For Spring Foragementioning
confidence: 99%
“…Cover crops deliver multiple ecosystem services [1], such as reduced nutrient leaching [2,3] through nutrient uptake [4], reduced soil erosion [5], enhanced soil fertility [6] and improved soil-water dynamics [7], weed suppression [8,9], and forage production [10]. Cover crops are promoted as a best management practice to avoid water quality impairment [11] and as a soil management tool [5], but their adoption remained low by the mid 2010s [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dhillon et al (2019) recognized that CP content was decreased with increase in age of crop plant. Landry et al (2019) reported that winter cereal cover crops such fase de grano lechoso, el rendimiento de forraje verde y de materia seca fue mayor en N 3 C 3 en comparaciĂłn con el resto de los tratamientos, seguido de N 2 C 3 durante los años consecutivos Las plantas tratadas con dosis de nitrĂłgeno de primer nivel tienen mĂĄs hojas y, por lo tanto, producen la mayor relaciĂłn hoja/tallo, lo que conduce a un mĂĄximo rendimiento de forraje verde. En contraste con nuestros hallazgos, Khan et al (2014) reportaron que bajo condiciones agroclimĂĄticas de Sargodha, PakistĂĄn, los mayores rendimientos de forraje en la avena pueden deberse probablemente a su mayor ĂĄrea foliar, responsable de una mayor eficacia fotosintĂ©tica, teniendo una alta aptitud para acaparar productos asimilables de la fotosĂ­ntesis.…”
Section: Jamil Et Alunclassified